The impact of the Hamas-Israel conflict on the U.S. defense industry stock market return - Jeroen Klomp (PLoS ONE, 2025)
On October 7th, 2023, Hamas carried out a terrorist attack on Israel. The Israeli government promptly retaliated the attack with massive bombing and a major military operation in the Gaza Strip. Following these events, a period of uncertainty started about the potential escalation of the internal conflict into a widespread regional conflict, or at least causes a threat to the fragile peace in the Middle East. This uncertainty was even further exacerbated as many regional leaders strongly condemned the actions of Israel. This study investigates whether the equity value of U.S. defense companies stands to gain in the short run from the risk of regional peace instability, given the anticipated increase in demand for arms. For this purpose, we rely on different approaches to capture the threat to regional peace caused by the internal conflict, including one based on the intensification of internet searches containing information about the Hamas-Israeli conflict. The key findings of this study unequivocally reveal that there is a significant positive relationship between the conflict intensity and the daily stock market returns of U.S. arms-producing firms. This result may suggest that investors are inclined to believe that the internal conflict is a serious threat to the regional peace, thereby enhancing the business prospects of the U.S. defense industry, as the largest arms supplier in the area.